Community Experiences of Serious Organised Crime in Scotland - Atkinson, Colin (2018)
This summary sets out key findings from a research project that aimed to explore the community experiences of serious organised crime ( SOC) in Scotland. The study sought to answer the following questions: 1) What are the relationships that exist between SOC and communities in Scotland? 2) What are the experiences and perceptions of residents, stakeholders and organisations of the scope and nature of SOC within their local area? and 3) How does SOC impact on community wellbeing, and to what extent can the harms associated with SOC be mitigated? The work involved in-depth qualitative research, to understand both direct and indirect forms of harm. Key points pertaining to the research and its results are as follows: - The study involved the selection of three community case study sites based on a typology of ' SOC-affected' communities. These sites were based in varying urban and semi-urban settings. - The impact of SOC at a more 'diffuse' national level was explored via research in a range of smaller case study sites and via interviews with national stakeholders. This included a consideration of SOC impacts in rural and remote areas, and on populations that were not concentrated in any defined geographic community. - The case study areas were selected on the basis of pre-existing academic and policy literature, an initial set of interviews with key experts, and on the basis of aggregated and anonymised intelligence summaries provided by Police Scotland. - 188 individuals participated in the study, which mostly involved semi-structured qualitative interviews, but also a small number of focus groups, unstructured interviews and observational research. Interviews were conducted with residents, local businesses, service providers, community groups, and national organisations, as well as with a small number of individuals with lived experience of SOC. - Interviews comprised of questions about: the relationship between SOC and communities; the experiences and perceptions of residents and local service providers as to the nature and extent of SOC; and the impact of SOC on community wellbeing. - Preliminary findings were presented back to a sub-sample of 33 community residents and representatives, across three of the case study areas, through a feedback method called 'co-inquiry'. This involved the organisation of events designed to assess the integrity of the findings, and elicit reflections on the implications of the findings for potential actions